2011
DOI: 10.1523/jneurosci.1420-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Hypertonicity Sensing in Organum Vasculosum Lamina Terminalis Neurons: A Mechanical Process InvolvingTRPV1But NotTRPV4

Abstract: . At present, the mechanism by which hypertonicity modulates cation channels in OVLT neurons is unknown, and it remains unclear whether Trpv1 and Trpv4 both contribute to this process. Here, we show that physical shrinking is necessary and sufficient to mediate hypertonicity sensing in OVLT neurons isolated from adult mice. Steps coupling progressive decreases in cell volume to increased neuronal activity were quantitatively equivalent whether shrinking was evoked by osmotic pressure or mechanical aspiration. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
104
3
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(112 citation statements)
references
References 46 publications
3
104
3
2
Order By: Relevance
“…These signals influence OVLT to act on the MNCs in either an inhibitory or excitatory fashion, in addition to the OVLT's osmosensing regulation. Similar to MNC osmosensing, the neurons of the OVLT are mechanically regulated, with hypertonic cell shrinkage leading to increased firing [30]. This osmomechanical regulation is mediated via TRPV1 channels which are non selective cation channels.…”
Section: Osmolal Regulationmentioning
confidence: 99%
See 2 more Smart Citations
“…These signals influence OVLT to act on the MNCs in either an inhibitory or excitatory fashion, in addition to the OVLT's osmosensing regulation. Similar to MNC osmosensing, the neurons of the OVLT are mechanically regulated, with hypertonic cell shrinkage leading to increased firing [30]. This osmomechanical regulation is mediated via TRPV1 channels which are non selective cation channels.…”
Section: Osmolal Regulationmentioning
confidence: 99%
“…This osmomechanical regulation is mediated via TRPV1 channels which are non selective cation channels. The TRPV channels are mechanically activated due to cell shrinkage [30]. Other influences on ADH secretion include sleep cycle, and thermal regulation.…”
Section: Osmolal Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…ANG II acts on angiotensin type I receptors (AT 1 -R), which are present in neurons and which by activating two different intracellular pathways have been proposed to lead to either water or sodium intake (31,(75)(76)(77)86). Hyperosmolarity activates nonselective cation channels (e.g., transient receptor potential vanilloid-related channels) and hypernatremia activates Na x channels (25,26,84,118,119).The NTS contains the first synapse in the central nervous system (CNS) that receives input from systemic visceral receptors. Signals that arise from peripheral high-and lowpressure baroreceptors (23, 30) can inhibit thirst and sodium appetite when blood volume is expanded or blood pressure is high and facilitate thirst and salt intake when pressure and volume are low (79,112,128,129).…”
mentioning
confidence: 99%
“…Subsequent studies have shown that TRPV1 2/2 mice show altered mechanical hypersensitivity in colonic afferents (Jones et al, 2005;De Schepper et al, 2008), bladder afferents (Daly et al, 2007), urothelial cells (Birder et al, 2001;Birder et al, 2002), osmosensory neurons (Ciura et al, 2011) and muscle (Ro et al, 2009). Mechanical activation of TRPV1, through either direct or indirect mechanisms, might be involved in the mechanics of Ca 2+ influx during the migration of epidermal keratinocytes.…”
Section: Discussionmentioning
confidence: 99%